Glucose metabolism and glycosylation link the gut microbiota to autoimmune diseases - Wang, Lu; Xu, Haojie; Yang, Huaxia; Zhou, Jiaxin; Zhao, Lidan; Zhang, Fengchun (Frontiers in Immunology, 2022)
Carbohydrates serve as important energy sources and structural substances for human body as well as for gut microbes. As evidenced by the advances in immunometabolism, glucose metabolism and adenosine triphosphate (ATP) generation is deeply involved in immune cell activation, proliferation, and signaling transduction as well as trafficking and effector functions, thus contributing to the immune responses programming and assisting the host adaption to microenvironment changes. Increased glucose uptake, aberrant expression of glucose transporter 1(e.g., GLU1) and abnormal glycosylation patterns have been identified in autoimmunity and are suggested partially responsible for the dysregulated immune response and the modification of gut microbiome composition in the autoimmune pathogenesis. The interaction between gut microbiota and host carbohydrate metabolism is complex and bidirectional. Their impact on host immune homeostasis and the development of autoimmune diseases remains to be elucidated. This review summarized the current knowledge on the crosstalk of glucose metabolism and glycosylation in the host with intestinal microbiota, and discussed their possible role in the development and progression of autoimmune diseases. Potential therapeutic strategies targeting glucose metabolism and glycosylation in modulating gut ecosystem and treating autoimmune diseases were discussed as well.